Pengembangan Multimedia Interaktif Canva Untuk Meningkatkan Motivasi Belajar Siswa di SMPN 1 Pariangan - Safitri, Jihan; Yenti, Isra Nurmai; Herlina, Elda; Nari, Nola (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The problem in this articlel is the low motivation to learn mathematics of SMPN 1 Pariangan students due to the lack of teaching materials and media in the SPLDV material. To overcome this, teaching media are needed that can increase student learning motivation. This study aims to produce valid, practical, and effective Canva-based interactive multimedia. This study uses the Research & Development method with a 4-D development model, but the dissemination stage was not implemented. Data were collected through questionnaires with instruments in the form of validation sheets, teacher response questionnaires, students, and motivation questionnaires. Data analysis used the validation percentage formula and N-Gain. The results showed that Canva-based interactive multimedia had a very valid level of validity (90.24%). The practicality test showed that the teacher response questionnaire (92.58%) and students (90.63%) were in the very practical category. Effectiveness on learning motivation showed an N-Gain score of 0.616 (moderate category) or 61.6% (quite effective). Permasalahan dalam artikel ini adalah rendahnya motivasi belajar matematika siswa SMPN 1 Pariangan akibat kurangnya bahan dan media ajar pada materi SPLDV. Untuk mengatasinya, dibutuhkan media ajar yang dapat meningkatkan motivasi belajar siswa. Penelitian ini bertujuan menghasilkan multimedia interaktif berbasis Canva yang valid, praktis, dan efektif. Penelitian ini menggunakan metode Research & Development dengan model pengembangan 4-D, namun tahap disseminate tidak dilaksanakan. Data dikumpulkan melalui angket dengan instrumen berupa lembar validasi, angket respon guru, siswa, dan angket motivasi. Analisis data menggunakan rumus persentase validasi dan N-Gain. Hasil penelitian menunjukkan multimedia interaktif berbasis Canva memiliki tingkat validitas sangat valid (90,24%). Uji praktikalitas menunjukkan angket respon guru (92,58%) dan siswa (90,63%) dalam kategori sangat praktis. Efektivitas terhadap motivasi belajar menunjukkan skor N-Gain 0,616 (kategori sedang) atau 61,6% (cukup efektif).